Managemen Karir Guru Min 11 Boyolali Dalam Upaya Meningkatkan Mutu Pendidikan - Arianty, Rizky (Universitas Nahdlatul Ulama Pasuruan, 2025)
The rapid development of technology and science has a significant impact on the adjustment and improvement of the curriculum. One negative impact of curriculum changes is causing a decline in the quality of education at every level, which is due to uneven readiness among educational institutions. Therefore, schools must be able to manage educators so that the quality of education can improve. This research aims to discuss the career management of teachers at MIN 11 Boyolali in enhancing the quality of education. The research method used is qualitative research with data collection through interviews, observation, and documentation. The research results show that MIN 11 Boyolali aims to improve the quality of education by implementing three programs: qualification, certification, and training.